The emerging role of EM simulation in IEEE 802.16e mobile WiMAX power amplifier design - Syuhaimi, Kassim; Fareq, Malek, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/